Electrophysiological approaches to informing therapeutic interventions with deep brain stimulation - Atefeh Asadi; Alex I. Wiesman; Christoph Wiest; Sylvain Baillet; Huiling Tan; Muthuraman Muthuraman (npj Parkinson's Disease)
Abstract Neuromodulation therapy comprises a range of non-destructive and adjustable methods for modulating neural activity using electrical stimulations, chemical agents, or mechanical interventions. Here, we discuss how electrophysiological brain recording and imaging at multiple scales, from cells to large-scale brain networks, contribute to defining the target location and stimulation parameters of neuromodulation, with an emphasis on deep brain stimulation (DBS).